Study of renal and ophthalmic manifestations in hypertensive disorders of pregnancy and its outcome - Tharihalli, Chandrashekhar; Giraddi, Raju V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background:Hypertensive diseases of pregnancy are commonly manifested in renal and ocular changes. Proper evaluation of findings provided by urine analysis, renal function test, urine output and examination of the optic fundi and visual fields may help in assessing the severity and the need for intervention. The primary objective was to determine the prevalence of retinal and renal manifestations in hypertensive disorders in pregnancy and feto-maternal outcome. Methods: This prospective study was conducted in VIMS, Ballary, Karnataka, India between 1st March 2014 to 28th February 2015. Detailed history and ocular examination with direct fundoscopy and renal parameters were noted on the mothers admitted and their correlation with feto maternal outcome studied. Results: 432 patients were included in the study, 41.7% had retinopathy changes on fundoscopy, 31.3% patients had Grade I hypertensive changes. Grade II, III and IV changes were seen in 4.2%, 2.1% and 4.2% respectively. There was an increase in blood uric acid levels with increase in severity of preeclampsia. The incidence of IUFD (8.3%), still born (8.3%) and need for NICU admission were significantly more with the severity of preeclampsia. Conclusions: Cases of hypertensive disorders in pregnancy with visual disturbances and headache are commonly associated with retinal changes. It is essential to examine every pre-eclampsia patient for ocular manifestations, which is helpful in the management of patient. Maternal urine protein test helps to detect the glomerular insult in the kidney and is a strong predictor of maternal and fetal complications.